Determination of Multiple Fluorescent Brighteners in Human Plasma Using Captiva EMR-Lipid Clean-Up and LC-MS/MS Analysis - Yubing Yan; Bowen Liang; Jiawen Yang; Qing Deng; Xiaoying Liang; Hui Chen; Bibai Du; Lixi Zeng (Toxics)
Fluorescent brighteners (FBs) are a class of chemicals extensively used in industrial and consumer products. Their environmental occurrences and potential health risks have raised significant concerns. However, the lack of analytical methods for FBs in human samples has hindered the accurate assessment of internal exposure levels. Addressing this gap, this study developed and validated a novel method for the simultaneous determination of 13 FBs at trace levels in human plasma using solid-phase extraction combined with HPLC-MS/MS. The method employed EMR-Lipid SPE columns, which can selectively adsorb phospholipids for plasma sample pre-treatment. Detection was achieved through positive ion electrospray ionization (ESI) in multiple reaction monitoring (MRM) modes. The results showed that all 13 FBs exhibited good linearity within their respective ranges, with correlation coefficients (R2) greater than 0.992. The method quantitation limits (MQLs) of the FBs ranged from 0.012 to 0.348 ng/mL, and the spiked recovery rates ranged from 61% to 98%. The method was successfully applied to analyze 10 adult plasma samples, detecting 10 FBs with total concentrations ranging from 0.221 to 0.684 ng/mL. This study provides a reliable analytical method for determining FBs in human plasma, providing a basis for further research on human internal exposure to FBs and associated health risk assessments.